2004
DOI: 10.1002/cncr.20728
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of breast‐conserving treatment of breast carcinoma in women with germline mutations in BRCA1 or BRCA2

Abstract: BACKGROUND. Although BRCA1 and BRCA2 were identified in 1994 and1995,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 22 publications
(15 reference statements)
4
59
1
6
Order By: Relevance
“…The appropriateness of breast-conserving therapy for women with hereditary breast carcinoma is an area of ongoing discussion. Women with BRCA-associated breast carcinoma who undergo breast-conserving surgery appear to have a risk of metachronous ipsilateral breast carcinoma similar to that reported for young women without known mutations [17]. The indications for unilateral mastectomy in this group of women should therefore be the same as for women with nonhereditary carcinoma.…”
Section: Genetic Counseling and Management Of Women With Hereditary Bsupporting
confidence: 53%
See 1 more Smart Citation
“…The appropriateness of breast-conserving therapy for women with hereditary breast carcinoma is an area of ongoing discussion. Women with BRCA-associated breast carcinoma who undergo breast-conserving surgery appear to have a risk of metachronous ipsilateral breast carcinoma similar to that reported for young women without known mutations [17]. The indications for unilateral mastectomy in this group of women should therefore be the same as for women with nonhereditary carcinoma.…”
Section: Genetic Counseling and Management Of Women With Hereditary Bsupporting
confidence: 53%
“…However, a significant risk of contralateral breast carcinoma and possibly late metachronous ipsilateral breast carcinoma may prompt consideration of bilateral mastectomy as a preventive measure [17]. A study by Garcia-Etienne et al [18] showed that the risk of ipsilateral breast tumor recurrence after breast-conserving surgery in BRCA1/2 mutation carriers was increased compared with patients who had sporadic breast cancer.…”
Section: Genetic Counseling and Management Of Women With Hereditary Bmentioning
confidence: 99%
“…We use the American Society of Clinical Oncology (ASCO) and CAP guidelines for performance and evaluation of ER, PR and Her2/ neu status in breast cancer (Harris et al, 2007;Wolff et al, 2007). As BRCA1 and BRCA2 mutations (Angliana Breast Cancer Study Group, 2000;Tan et al, 2008) are common in female breast carcinoma, we intend to start molecular testing for these mutations by the end of 2014, so that we can offer this valuable information to our clinicians and help in the better management of these cancers in women with family history of breast carcinoma, and to determine the choice between close follow-up and prophylactic mastectomy (Robson et al, 2005;Robson and Offitt, 2007). BRCA1 protein expression can be detected immunohistochemically and cytoplasmic expression may be associated with unfavorable prognosis (Rakha et al, 2008).…”
Section: Breast Pathologymentioning
confidence: 99%
“…5 In developing countries, the average age at diagnosis of breast cancer may be younger than in developed countries, as data from eastern populations suggest. 7,12,14 In eastern Africa, it is estimated that the age standardised incidence rates (per 100,000 women) is 19.5 . 9 In western Africa it is 27.8, in middle Africa 16.5 and 33.4 in southern Africa.…”
Section: Breast Cancer Incidence Rates In Africa As a Developing Contmentioning
confidence: 99%
“…But due to the lifetime risk of contralateral breast cancer and late ipsilateral breast cancer, bilateral mastectomy as prophylaxis should be a serious consideration. 12 Breast conserving treatment need not be ruled out as a treatment option for young women in the developed or developing world, as long as the patient is fully aware of the high risk for local recurrence. There are no studies that show that overall survival is negatively impacted in patients receiving BCT.…”
Section: Breast Cancer Incidence Rates In Africa As a Developing Contmentioning
confidence: 99%